ANALISIS IMPLEMENTASI SISTEM PENJAMINAN MUTU DAN AKREDITASI PADA PROGRAM STUDI PENDIDIKAN JASMANI KESEHATAN DAN REKREASI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS LAMBUNG MANGKURAT BANJARMASIN - Sunarno Basuki (Multilateral : Jurnal Pendidikan Jasmani dan Olahraga, 2013)
Universities have an important role in providing competitive and quality human resources. Therefore, the need for quality assurance and accreditation system for universities as evidence that the process of forming human resources guaranteed. Health Physical Education Studies Recreation Departemen of  Lambung Mangkurat University is expected to become the center of education and research in the field of human resource development of health physical education and  recreation in  South Kalimantan. As a policy, the Internal Quality Assurance System (SPMI) should be implemented.This study attempted to answer how the implementation process and factor constraints faced during the implementation of the SPMI. By using a qualitative research design, this study put forward some conclusions as follows: (a) The implementation process of internal quality assurance system in the course of health physical education and recreation  FKIP  UNLAM  not  run  well.  The  system  is  still  prominent  in  the interpretation stage, less than the maximum at the application stage and (b) some of the factors that make implementation constraints internal quality assurance system in the course of health physical education and recreation FKIP UNLAM not run well, namely: communication factors that are less intensive, inadequate human resources, the structure of the firm and the attitude or the commitment of officials and professors less than the maximum. Keywords: standard internal quality assurance, accreditation and implementation.